Hunting the 1918 Flu - Duncan, Kirsty (Book collections on Project MUSE., 2003)
"In 1918 the Spanish flu epidemic swept the world and killed an estimated 20 to 40 million people in just one year, more than the number that died during the four years of the First World War. To this day medical science has been at a loss to explain the Spanish flu's origin." "Responding to sustained interest in this medical mystery, Hunting the 1918 Flu presents a detailed account of Kirsty Duncan's experiences as she organized an international, multi-discipline scientific expedition to exhume the bodies of a group of Norwegian miners buried in Svalbard, all victims of the flu virus." "Duncan raises questions not only about public health, epidemiology, the ethics of science, and the rights of subjects, but also about the role of age, gender, and privilege in science. While her search for the virus has shown promising results, it has also revealed the dangers of science itself being subsumed in the rush for personal acclaim."--Jacket.